2022
DOI: 10.1039/d1ee03225a
|View full text |Cite
|
Sign up to set email alerts
|

Non-fullerene acceptors with direct and indirect hexa-fluorination afford >17% efficiency in polymer solar cells

Abstract: The rational molecular design of non-fullerene acceptors (NFAs) in organic solar cells (OSCs) can profoundly influence photovoltaic (OPV) performance. NFA fluorination has to date proven beneficial to cell performance. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…Thus, PM6:BT-BO-L4F OPV device had a higher J SC (27.8 mA cm –2 ) and PCE (16.0%) than the reference PM6:Y6 OPV device ( J SC = 26.0 mA cm –2 and PCE = 14.5%). The authors further reported incorporation of trifluoromethyl onto the terminal benzoindanone group as an indirect fluorination strategy to compare with direct fluorination on the benzoindanone . Similarly, Wei et al synthesized BTP-C9-N2F and BTP-C9-N4F, which contain monofluorinated and difluorinated benzoindanones as terminal A groups, respectively.…”
Section: Recent Progress In the Development Of Nfa Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PM6:BT-BO-L4F OPV device had a higher J SC (27.8 mA cm –2 ) and PCE (16.0%) than the reference PM6:Y6 OPV device ( J SC = 26.0 mA cm –2 and PCE = 14.5%). The authors further reported incorporation of trifluoromethyl onto the terminal benzoindanone group as an indirect fluorination strategy to compare with direct fluorination on the benzoindanone . Similarly, Wei et al synthesized BTP-C9-N2F and BTP-C9-N4F, which contain monofluorinated and difluorinated benzoindanones as terminal A groups, respectively.…”
Section: Recent Progress In the Development Of Nfa Materialsmentioning
confidence: 99%
“…The authors further reported incorporation of trifluoromethyl onto the terminal benzoindanone group as an indirect fluorination strategy to compare with direct fluorination on the benzoindanone. 181 Similarly, Wei et al synthesized BTP-C9-N2F and BTP-C9-N4F, which contain monofluorinated and difluorinated benzoindanones as terminal A groups, 182 respectively. They found that terminal A groups with longer πconjugation lengths had higher-lying HOMO energy levels than those with shorter π-conjugation lengths and, thus, had a lower nonradiative V OC loss.…”
Section: Tailoring the Electron-accepting Strength Of Flanking A Term...mentioning
confidence: 99%
“…The replacement of fullerene derivatives by non-fullerene acceptors (NFAs) has helped ascend the PCE of single-junction OPV to beyond 18% 5 11 , closing the gap with other PV technologies 12 . Meanwhile, this strategy also improves the OPV stability by overcoming the molecular diffusion and aggregation of spherical fullerene acceptors 13 15 . However, the trade-off between PCE and stability still remains in bulk-heterojunction (BHJ) OPV, because of the meta-stable morphology in the active layer.…”
Section: Introductionmentioning
confidence: 99%
“…7a), solar cells based on PM6:Y6-Se-4Cl yielded a PCE of 15%. Marks et al 96 compared direct skeletal fluorination (BTF) and indirect trifluoromethyl fluorination (BTFM) of end group of Y6 (Fig. 7a).…”
Section: Polymer Donor/small Molecule Acceptor Oscsmentioning
confidence: 99%